HOW EU MEMBER STATE INTERESTS PERMEATE INTO EUROPEAN COMMISSION DECISION-MAKING: A ROLE THEORETICAL APPROACH TO THE COMMISSION’S CABINET SYSTEM - (:unkn) unknown (My University, 2019)
Although the European Commission has to be immune to member stateinfluences in order to act on behalf of the whole Union, historically its cabinets havebeen portrayed as national enclaves and even ‘mini-Councils’, constituting a venuefor national interests to penetrate in European Commission decision-making.Despite the Kinnock reforms which led to the denationalisation of cabinets,empirical evidence whether denationalisation has an effect on the cabinets’ role asaccess points for national interests still needs to be discovered. This article claimsthat in order to test whether the denationalisation of European Commission’scabinets has indeed prevented national interests to be represented in EuropeanCommission decision-making, the focus should be on agency rather than structure.Role theory has to contribute significantly in this regard.

Avrupa Komisyonu’nun Birliğin ortak çıkarları adına çalışabilmesi için ulusal çıkarlara karşı bağışık olması gerekir. Buna rağmen tarihsel olarak Komisyon içindeki kabineler, üye devletlerin kendi ulusal çıkarlarını Komisyon kararlarına sızdırabildiği ve üye devletler tarafından kuşatılmış ‘mini-Konsey’ler’ olarak tanımlanır. Her ne kadar Kinnock reformları kabinelerin ulusalsızlaşmasını sağlamış olsa da, bu ulusalsızlaşmanın kabinelerin ulusal çıkarlar için bir erişim noktası olması üzerindeki etkisinin henüz araştırılması gerekir. Bu makale Avrupa Komisyonu kabinelerinin ulusalsızlaştırılmasının gerçekten ulusal çıkarların Komisyon kararlarında temsil edilmesinin engelleyip engellemediğini araştırabilmek için rol teorik bir yaklaşımın uygulanması gerektiğini iddia ediyor.
Ulusal Çıkarların Avrupa Komisyonu Karar Alma Sürecine Sızması: Komisyonun Kabine Sistemine Rol Teorik bir Yaklaşım
Keywords: İktisat; Tarih; Uluslararası İlişkiler; Hukuk; Siyasi Bilimler